Actividades lúdicas y su impacto en educación inicial del nivel I de la Unidad Educativa Babahoyo, cantón Babahoyo, provincia los Ríos - Rumiguano Caluña, Jenny Margoth (2018)
The present final report of the research project is oriented to the enrichment of the learning in the initial education of the level I of the Educational Unit "Babahoyo", through playful activities that promote the interest and the desire to learn, where the playful is the tool essential for the process of integral formation of each student. The experience starts from the observation that was made to know the reality that the educational community was living, until achieving their awareness on the importance of innovating the pedagogical task within the classrooms of the youngest. To carry out this process that led to the creation of a proposal, the problematic related to the little inclusion of the playful in the learning process of the children of the transition degrees is taken into account; from which the pedagogical intervention is proposed with the intention of generating a change of thought with which one can act inside and outside the classroom. In this way, with the proposal, activities are developed according to the ages, interests and needs of the students, but especially directed to the strengthening of their learning process and adaptation to the educational system. The proposal achieves the interrelation between the teacher and his students, with practical, simple and fun tools to strengthen the learning and the integral development in the children of the preschool level.